Adjuvant effects of trehalose dimycolate on the antibody response to type III pneumococcal polysaccharide. - Baker, P J (1989)
Treatment with trehalose dimycolate (TDM) increases the magnitude of the immunoglobulin M (IgM) antibody response of mice to type III pneumococcal polysaccharide (SSS-III). Such enhancement is demonstrable over a wide range of immunizing doses and does not require thymus-derived (T) cells to be elicited. Although young adult mice immunized with SSS-III do not usually make anti-SSS-III antibodies of the IgG1 and IgG3 classes, antibodies of one or both isotypes were produced after immunization and treatment with TDM and/or monophosphoryl lipid A (MPL); the additive nature of the effect produced by both TDM and MPL suggests that the two immunomodulators act by different mechanisms. TDM and MPL have different effects on the induction and expression of low-dose immunological paralysis, a form of unresponsiveness known to be mediated by suppressor T cells. The relevance of these findings to the modes of action of TDM and MPL is discussed.